(untitled) (Damascus University Journal for engineering sciences, 2021)
In the event of detection of a disease or a study of the development of a disease and after a clinical examination, the doctor will request to perform clinical laboratory tests (quantitative or qualitative) associated with this disease before moving to other ways to treat this disease. The more accurate the results of laboratory tests, the more effective the treatment, and there are several ways to confirm this precision and accuracy because they have significant impact on the quality of diagnosis and therefore on treatment. Statistical methods based on the study of the basic statistical parameters such as mean value, standard deviation and coefficient of variation, coupled with the factor of confidence and accuracy required (usually 95%) for laboratory tests. This is useful in evaluating the accuracy and precision, which gives an indication of the state of laboratory results. Causes of inaccuracy can be due to several reasons. The most important of which are: the technician is not qualified enough, the device needs to re-set, the reagents are ineffective, the absence of a Blanc or the Blanc is incorrect and do not performing the complete series of necessary calibration. The importance of this paper is obvious during the study of reliability and analysis of the results of tests statistically, such as study accuracy, precision and control, sensitivity and reliability quality. There is also a great importance in the accuracy of the preparation and measurement of the parameters of laboratory analysis. In conclusion, experiments conducted on blood glucose analysis increased the accuracy and validity of the measurement to more than 97%.